Developing national strategies for soil fertility - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The decline in soil fertility is often an insidious and imperceptible process. By the time the decline is noticed it is already at a stage difficult to reverse.The International Fertilizer Development Center together with the World Bank organized a...